Cataclysmic variable stars - Warner, Brian (Cambridge astrophysics, 1995)
The study of cataclysmic variables - interacting binary stars containing a white dwarf accreting from an orbiting companion - is undergoing an exciting renaissance, as it embraces observations at all wavelengths. Cataclysmic variables allow, in particular, the direct and detailed study of equilibrium and non-equilibrium accretion discs; in turn these developments also help in our understanding of X-ray binaries, black holes and active galactic nuclei. This timely volume provides the first comprehensive survey of cataclysmic variable stars, integrating theory and observation into a single, synthesised text. An introductory chapter gives the historical background of studies of cataclysmic variables. The author then goes on to give an up-to-date review of both the observations (at all wavelengths, and over all time-scales), the theories, the models of the structures and accretion processes believed to be involved. A very detailed bibliography is also provided to guide the reader to pertinent primary literature